Detailed characterization of aeration in lubricating oils by an ultrasonic approach. (November 2022) - Zhan, Che; Saint-Jalmes, A.; Receveur, M.; El Bahi, H.; Rondelez, F.; Leroy, V.
Abstract: Lubricating oils get aerated during their use, reducing their efficiency and stability. Deaerating agents are generally added to reduce aeration. Understanding the mechanisms by which these additives set the gas fraction in oil is crucial for the development of optimal formulation. Here we present experiments performed on a Flender test apparatus in which ultrasonic probes are incorporated. We present the technique and demonstrate that it provides the gas volume fraction but also information on the bubble size during the aeration process. Thanks to this measuring technique, new insights on the dynamics of both aeration and de-aeration are gained. As an example, we show how these parameters are affected by the presence of four different additives in a specific reference oil. Highlights: We conducted experiments on air entrainment by the rotation of a gear in an oil bath. Ultrasonic measurements can give access, in real time, to the level of aeration of oil and the typical size of the bubbles. Experiments with different deaerating additives reveal that they have a strong effect on the size of the bubbles entrained.